STUDI PERBAIKAN CARA PENYADAPAN KOPAL DI KPH SUKABUMI - Soenarno Soenarno; Maman Mansyur Idris; Zakaria Basari (Jurnal Penelitian Hasil Hutan, 1984)
Copal from Agathis tree has been one of  important  forest  products, not only as export commodity but also as raw material for some induatries. In the last few years however production  in  this country  began to decrease, due to inefficient  tapping by the forest worker.Because of  this reason a study on the tapping procedure is necessary. Thia report deals with a preliminary study on  the present  “quarre”  type  of  tapping procedure commonly  adopted  by the forest  worker. The locality chosen was Gede Barat Sub forest district at Sukabumi, West Java.Three factors were chosen  for the tapping study, namely the effect  on of resin productivity  of the location of the wound with respect to west and east direction (factor A), time of tapping (factor B) and type of wound covering (factor C).  The result of this study show that :Covering of tap wound does not cause incoveniences   to the worker.Resin productivity is not significantly affected by the wound location.The highest production of the resin per tree comes from the wound cut in the morning and covered with black coloured polyethelene sheet.